First episode-psychosis: Short- and long-term outcomes and related features predicting the transition to schizophrenia. (1st June 2022) - Jabeur, M.; Gassab, L.; Boughamoura, S.; Mhalla, A.; Zaafrane, F.; Gaha, L.
Abstract : Introduction: The occurrence of a first episode-psychosis in adolescents or young adults represents a difficult struggle with an uncertain and divergent outcome, since the clinician does not have at his disposal the clinical elements sufficient to predict these different disease trajectories. Objectives: Our aims are to describe the socio-demographic, clinical characteristics and the short and long-term outcomes of a first episode-psychosis and to identify the predictive factors of the transition to schizophrenia. Methods: We conducted a retrospective study about 117 patients hospitalized for a first episode-psychosis in the Psychiatric Department of Monastir (Tunisia). Sociodemographic and clinical features were collected using a pre-established form. Results: First-episode psychosis affected young male subjects with low educational level. Stressors were present in 54.7%. An 8-week prodromal phase preceded the onset of the disorder in 59%. The disorder course included diagnosis of: Brief psychotic disorder (32.5%), schizophrenia (31.6%) and bipolar disorder (18.8%). The short-term outcome was characterized by a complete remission rate of 58.1% at 3 months and 37.6% at 6 months. The long-term outcome was marked by a high rate of lost to follow-up: 70.8% after 5 years. The transition to schizophrenia was linked to the presence of delirium of influence and the absence of favorable course at 3 months. Conclusions: Our results led to the identification of the profile of patients with a first episode-psychosis and the factors correlated with a diagnosis of schizophrenia. Indeed, the determination of risk factors would make it possible to adapt earlier the care. Disclosure: No significant relationships.